The adventures of Tom Sawyer - Twain, Mark 1835-1910; Clemens, Samuel Langhorne 1835-1910 (New York : Dell Publishing, 1967)
This special edition is for readers for whom english is a second language. It can be read by anyone who has learned 1,000 words of english.
Glossary.
Keywords: Novelas; Estados Unidos De America; Literatura Norteamericana